TRANSFORMASI PEMBELAJARAN MELALUI E-LEARNING : (MEMAHAMI DAN MENGEVALUASI E-LEARNING DARI PERSPEKTIF METAKOGNITIF) - Farida, Eni (DINAMIKA DOTCOM, 2011)
The use of computer and internet technology has been utilized for all aspects of life, legal, social, economic and educational aspects. This led to new learning system known as e-learning, which requires students and teachers interact online through the Internet, independent and creative in the learning process. E-learning system has the main features of the learning process in addition to learning through the Internet network connections, resources and learning materials are always up-to-date and abundant, has the benefits, advantages and benefits compared with traditional learning system. But also have weaknesses, especially for children and adolescents learning system that can be equipped with integrating the concept of traditional learning systems in schools and incorporate elements of independent learning through the internet in a structured way.Â Keywords : e-learning, metacognitive perspective